Síntese eletroquímica de filmes nanocompósitos de óxido de grafeno reduzido e hexacianoferratos de prata e de cobre visando à aplicação em sensores - Narciso, Laiz Cristina Diniz (2017)
This work shows the electrochemical synthesis of electrochemically reduced graphene oxide (erGO) and copper and silver hexacyanoferrates (CuHCF and AgHCF) through a dispersion of graphene oxide (GO) and Ag and Cu salts, using cyclic voltammetry. The second step of synthesis is also performed by cyclic voltammetry and aims at the deposition of hexacyanoferrate in the films described above. The study of pH of the electrolyte used in the films showed that the best responses regarding stability and current intensity for erGO/AgHCF and erGO/CuHCF are at pH 2 and 4, respectively. Through the studies of the effect of scan rate, the quasi-reversible character of erGO/AgHCF and reversible erGO/CuHCF was verified, in addition to revealing that the K + diffusion process controls the redox activity involved in both films. The efficacy of GO reduction was verified by XRD. Raman spectra were obtained to evaluate the reduction of GO and the presence of the hexacyanoferrates.The morphology of the materials was evaluated by SEM images, which showed for erGO/AgHCF nanoparticles in order of 250 nm and for erGO/CuHCF nanocubes of 120 nm in size. The voltammetric study of the films for the detection of captopril (CAP) and paracetamol (PA) was conducted and revealed the potential of the films as sensors. The chronoamperometric detection of CAP and PA was conducted in a batch injection analysis (BIA) system with the use of erGO/AgHCF. For PA was found a value of LD= 2.77 μmol L-1, LQ = 8.30 μmol L-1 and sensitivity of 0.063 μA L μmol -1.The detection of CAP presented two linear ranges, the first in the concentration range of 25-100 μmol L-1 with LD= 2.8 μmol L-1, LQ= 8.5 μmol L-1 and sensitivity of 0.0157 μA L μmol -1. The second linear range varies from 250 to 500 μmol L -1.